2005
DOI: 10.1007/s00262-005-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant Immunochemotherapy with polysaccharide K for patients with curatively resected colorectal cancer: a meta-analysis of centrally randomized controlled clinical trials

Abstract: The benefits of immunochemotherapy employing the biological response modifier polysaccharide K (PSK) for patients with curatively resected colorectal cancer was reassessed by means of a meta-analysis of data with center randomization from 1,094 patients enrolled in three clinical trials. In all three trials, patients were followed up for at least 5 years after surgery and enrollment of the last patient and outcomes for standard chemotherapy were compared with those for chemotherapy plus PSK. The endpoints were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…These results are confirmed by a metaanalysis of three trials (reported in 10 articles) involving 1, 094 subjects with colorectal cancer [87]. Those who took PSK showed a significant improvement in overall survival (RR 0.71; CI 0.55-0.90; P ¼ .006) and disease-free survival (RR 0.72; CI 0.58-0.90; P ¼ .003) [87]. Benefit of PSK was also demonstrated in a meta-analysis of 8,009 gastric cancer patients from eight randomized, controlled trials with an increased survival (HR 0.88; CI 0.79-0.98; P ¼ .0180) [88].…”
Section: Immune Modulationsupporting
confidence: 54%
See 1 more Smart Citation
“…These results are confirmed by a metaanalysis of three trials (reported in 10 articles) involving 1, 094 subjects with colorectal cancer [87]. Those who took PSK showed a significant improvement in overall survival (RR 0.71; CI 0.55-0.90; P ¼ .006) and disease-free survival (RR 0.72; CI 0.58-0.90; P ¼ .003) [87]. Benefit of PSK was also demonstrated in a meta-analysis of 8,009 gastric cancer patients from eight randomized, controlled trials with an increased survival (HR 0.88; CI 0.79-0.98; P ¼ .0180) [88].…”
Section: Immune Modulationsupporting
confidence: 54%
“…After 5 years of follow-up, the treated patient group also had a greater percentage of 5-year disease free survival (P ¼ .038) and a decreased relative risk of regional metastases (relative risk or RR 3.595; CI 1.518-8.518). These results are confirmed by a metaanalysis of three trials (reported in 10 articles) involving 1, 094 subjects with colorectal cancer [87]. Those who took PSK showed a significant improvement in overall survival (RR 0.71; CI 0.55-0.90; P ¼ .006) and disease-free survival (RR 0.72; CI 0.58-0.90; P ¼ .003) [87].…”
Section: Immune Modulationmentioning
confidence: 82%
“…Es gibt eine Reihe von Publikationen zum Einsatz von Heilpilzen bei kurativ behandelten Patienten mit kolorektalem Karzinom [1309,1310]. Diese Studien stammen aus China und Japan und sind in den Originalsprachen publiziert.…”
Section: Komplementäre Und Alternative Medizinunclassified
“…to have clinical effects in combined use for postoperative adjuvant chemotherapy for stomach (15,16) and colon (17)(18)(19) cancers.…”
Section: Discussionmentioning
confidence: 99%